2021
DOI: 10.1016/j.jtrangeo.2021.102982
|View full text |Cite
|
Sign up to set email alerts
|

Causes and effects between attitudes, the built environment and car kilometres: A longitudinal analysis

Abstract: Travel-related attitudes are believed to affect the connections between the built environment and travel behaviour. Previous studies found supporting evidence for the residential self-selection hypothesis which suggests that the impact of the built environment on travel behaviour could be overestimated when attitudes are not accounted for. However, this hypothesis is under scrutiny as the reverse causality hypothesis, which implies a reverse direction of influence from the built environment towards attitudes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Hence, the context of a non-major city area is generally (still) negative as regards to perceived accessibility of public transportation, in line with previous conclusions by Delbosc and Currie [2]. Our findings are also in line with a recently published study by van de Coevering et al [24], showing that distance to the nearest railway station is strongly associated with attitudes toward public transport. The study shows that a great distance has a strong negative influence, whereas a short distance has a positive influence on perceptions of public transport.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, the context of a non-major city area is generally (still) negative as regards to perceived accessibility of public transportation, in line with previous conclusions by Delbosc and Currie [2]. Our findings are also in line with a recently published study by van de Coevering et al [24], showing that distance to the nearest railway station is strongly associated with attitudes toward public transport. The study shows that a great distance has a strong negative influence, whereas a short distance has a positive influence on perceptions of public transport.…”
Section: Discussionsupporting
confidence: 92%
“…Leck [12] found that residential density is the strongest element of the built environment influencing travel mode choice. Negative associations between residential density and car ownership, VKT, and fuel consumption are further confirmed [13][14][15]. Increases in employment density are also found to negatively affect car ownership and use [16,17].…”
Section: E Impacts Of Built Environment On Car Dependencymentioning
confidence: 61%
“…Studies reveal that individual factors also have some impacts. For example, males and people with a higher education level are more inclined to drive more [15].…”
Section: Other Factors Influencing Modementioning
confidence: 99%
“…Because of their correlation with relatively stable behaviors (e.g., mode choice), we hypothesize that transport-related attitudes are predictable over time. While some have found this to be the case (van de Coevering, Maat, and Wee 2021), others have reported instability over time frames ranging from one week to two years (Sunkanapalli, Pendyala, and Kuppam 2000;Adams et al 2013;Thøgersen 2006).…”
Section: Questionsmentioning
confidence: 97%